Pengaruh Literasi Keuangan dan Literasi Digital terhadap Kinerja Usaha Mikro Kecil dan Menengah Melalui Kemampuan Manajerial: Studi Kasus Kabupaten Mamuju Sulawesi Barat - Nurdyanto, Sapto Dwi; Ismail, Tubagus; Sapiri, Muhtar (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to test and analyze the influence of financial literacy and digital literacy on the managerial abilities and performance of MSMEs, to analyze the influence of managerial abilities on the performance of MSMEs, to test and analyze the influence of financial literacy and digital literacy on the performance of MSMEs in Mamuju through managerial abilities as an intervening variable . This research uses a quantitative approach, taking a population of 365 MSME actors. Data collection techniques through questionnaires and documentation, with data analysis techniques using SmartPLS 3.2.9 analysis. The results of the research conducted prove that financial literacy has a positive and significant effect on managerial abilities, digital literacy has a positive and significant effect on managerial abilities. Financial literacy has a positive and significant effect on the performance of MSMEs, digital literacy has a positive and significant effect on the performance of MSMEs, managerial ability has a positive and significant effect on the performance of MSMEs in Mamuju Regency. The results of the indirect influence test found that managerial ability can mediate the influence of financial literacy on the performance of MSMEs in Mamuju Regency, as well as that managerial ability can mediate the influence of digital literacy on the performance of MSMEs in Mamuju Regency